2023
DOI: 10.3389/fphar.2023.1143158
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to pulmonary fibrosis following COVID-19

Abstract: Background: In the past few years, COVID-19 became the leading cause of morbidity and mortality worldwide. Although the World Health Organization has declared an end to COVID-19 as a public health emergency, it can be expected, that the emerging new cases at the top of previous ones will result in an increasing number of patients with post-COVID-19 sequelae. Despite the fact that the majority of patients recover, severe acute lung tissue injury can in susceptible individuals progress to interstitial pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Post-COVID pulmonary fibrosis, with an incidence ranging between 5 and 75%, contributes to the burden of chronic respiratory issues among survivors [ 89 ]. Its pathophysiology likely stems from the local proinflammatory environment caused by macrophage and immune cell infiltration in the lungs, which disrupts the natural homeostatic tissue-repair functions [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-COVID pulmonary fibrosis, with an incidence ranging between 5 and 75%, contributes to the burden of chronic respiratory issues among survivors [ 89 ]. Its pathophysiology likely stems from the local proinflammatory environment caused by macrophage and immune cell infiltration in the lungs, which disrupts the natural homeostatic tissue-repair functions [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified severe COVID-19 as a risk factor for residual pulmonary fibrosis, which is consistent with other studies [ 91 , 92 ]. Although there is no consensus on treatment, antifibrotic agents may benefit these patients [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung disease improved in approximately one third of patients in group D, and CD4+ T cells were implicated in this process. Regarding more advanced disease, the current view is that post-COVID fibrosis is non-progressive 53,65 ; however, further examination of its multi-factorial etiology, variable response to treatment 5,66 , long-term recovery, and post-acute immune drivers is warranted. The utility of CXCL13 as an early biomarker of lung disease, its role in divergent clinical courses, and potential for therapeutic targeting are all of interest in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the PINCER trial (NCT04856111) will compare these established antifibrotic treatments in a phase 4 head-to-head study evaluating the safety and efficacy of Pirfenidone versus Nintedanib. Several case reports have looked to assess the role of antifibrotics in acute COVID-19 illness with variable results [ 79 ]. A recently published study randomized symptomatic post-COVID-19 patients (at 12 weeks post discharge) to either Nintedanib or Pirfenidone.…”
Section: Management Strategies For Post-covid Ildmentioning
confidence: 99%